Educational Institution Strategic Plan Model - Erna Lutfijah; Nur Kholik Afandi; Husni Idris (Universitas Muhammadiyah Enrekang, 2023)
The strategic plan model is to explain the actions in the process of achieving the goals to be completed. This study aims to examine the strategic planning model. This study uses the library research method by collecting materials containing content about the strategic planning model. This study describes the meaning of strategic planning models, strategic planning components, and strategic planning models. The strategic planning steps include the following: 1) Set organizational goals and direction; 2) Learn about the environment inside and outside; 3) Formulate strategies; 4) Implement strategies; 5) Evaluate and monitor strategies. The strategic planning models are as follows: 1)